Optimalisasi kualitas sumber daya manusia melalui diversifikasi hasil perikanan pada masyarakat nelayan desa Gisik Cemandi - Anggraeni Rahmasari; Irwantoro Irwantoro (Journal of Business & Banking, 2016)
Gisik Cemandi is a village rich in marine natural resources but with low level of welfare. Natural factors that fluctuate fish season affect the income level of fishermen. This study uses Participatory Action Research descriptive to obtain information about the diversification of fishery products through the management and utilization of various resources contained in aquatic ecosystems and in the sea. Researchers conducted in-depth interviews with key informants are active fishermen who made the arrest to make ends meet. Development of coastal community access to economic resources meant to improve the diversification of sources of public income and simultaneously improve their welfare. These include the expansion of the choice of economic resources, such as business expansion and lending. Business opportunities besides fisheries sector needs to be opened wider is the field of agriculture, crafts, farm and transport services. This is important in order to open the public the opportunity to not only rely directly on natural resources, but also at the same time reducing the burden on nature.